Characterizing the Expression Patterns of Parkinson’s Disease Associated Genes - Li, Bin; Zhao, Guihu; Li, Kuokuo; Wang, Zheng; Fang, Zhenghuan; Wang, Xiaomeng; Luo, Tengfei; Zhang, Yi; Wang, Yijing; Chen, Qian; Huang, Yuanfeng; Dong, Lijie; et al. (Frontiers in Neuroscience, 2021)
Background The expression pattern represents a quantitative phenotype that provides an in-depth view of the molecular mechanism in Parkinson's disease (PD); however, the expression patterns of PD-associated genes (PAGs) and their relation to age at onset (AAO) remain unclear. Methods The known PD-causing genes and PD-risk genes, which were collected from latest published authoritative meta-analysis, were integrated as PAGs. The expression data from Genotype-Tissue Expression database, Allen Brian Map database, and BrainSpan database, were extracted to characterize the tissue specificity, inhibitory-excitatory neuron expression profile, and spatio-temporal expression pattern of PAGs, respectively. The AAO information of PD-causing gene was download from Gene4PD and MDSgene database. Results We prioritized 107 PAGs and found that the PAGs were more likely to be expressed in brain-related tissues than non-brain tissues and that more PAGs had higher expression levels in excitatory neurons than inhibitory neurons. In addition, we identified two spatio-temporal expression modules of PAGs in human brain: the first module showed a higher expression level in the adult period than in the prenatal period, and the second module showed the opposite features. It showed that more PAGs belong to the first module that the second module. Furthermore, we found that the median AAO of patients with mutations in PD-causing genes of the first module was lower than that of the second module. Conclusions In conclusion, this study provided comprehensive landscape of expression patterns, AAO features and their relationship for the first time, improving the understanding of pathogenesis, and precision medicine in PD.